Thinking on Your Feet: Strategies for Dealing with Difficult Situations - Dr. Walter H. Gmelch; Kelly Ward (Academic Chairpersons Conference Proceedings, 2017)
This session will offer chairs concrete ideas and strategies for dealing with difficult conversations using case studies and role-playing. Conversations with faculty, students, supervisors, and staff will be covered.
Keywords: strategies; difficult conversations; role-playing; faculty